Pandangan Akademisi Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten terhadap Praktik Poligami di Indonesia - Isma Amalia Sayyidah; Neli Amaliah; Hijjul Muhtarom; Humaeroh Humaeroh (International Forum of Researchers and Lecturers, 2026)
The practice of polygamy in Indonesia shows complex dynamics between normative provisions in Islamic teachings, national legal regulations, and social realities that develop in society. This research aims to answer the problem formulation regarding the views of Sharia Faculty academics regarding the meaning, objectives and impact of the practice of polygamy in Indonesia. The method used is empirical research (field research) with a qualitative approach through in-depth (semi-structured) interviews with Sharia Faculty lecturers who have competence in the field of Islamic family law, and is supported by secondary data in the form of statutory regulations and scientific literature. The research results show that polygamy is understood as a practice that is permitted under certain conditions with the main requirement of justice, and is placed as an exception to the principle of monogamy which is the basic principle in marriage law in Indonesia. The aim of polygamy is directed at beneficial aspects, such as maintaining morality, providing protection to vulnerable parties, and being a solution in certain situations. However, in practice polygamy tends to have various impacts, especially psychological, social and economic on wives and children. Therefore, the implementation of polygamy requires careful consideration and fulfillment of strict conditions so as not to cause injustice in family life.